Modern concepts in non-surgical esthetics; a review - Anca Pantea Stoian; Razvan Hainarosie; Catalina Pietrosanu; Andreea Rusescu; Liliana F. Andronache; Stana Paunica; Cristian Balalau; Teodora S. Pituru (Journal of Mind and Medical Sciences)
New non-surgical esthetics is the most dynamic field in contemporary medicine. At the same time, it is greatly influenced by our contemporary society. This paper reviews modern methods used in non-surgical esthetics, especially in Romania. From injectology and non-surgical face lifting to non-surgical body contouring, we analyzed all procedures performed by Romanian physicians, and we show the advantages and disadvantages of the advanced esthetic procedures. Injectology typically implies hyaluronic acid, botox and mesotherapy (for wrinkles and rejuvenation). Laser and radiofrequency treatment are used for wrinkles as well, with fewer unwanted adverse reactions and results exceeding those of injectables. Non-surgical lifting has gained more ground because it requires little recovery time and the results are very positive. Elective treatment for facial discoloration is the laser approach. For non-surgical body contouring, cryolipolisis, vacuum, radio frequency, and infrared systems have all revolutionized this part of esthetics, but each has limitations, and only after establishing the correct course of action, might we think of achieving favorable results and thus raising to the expectations of patients.